2004
DOI: 10.1111/j.1346-8138.2004.tb00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Evaluation of Intralesional 5% 5‐Fluorouracil in Condyloma Acuminata

Abstract: Condyloma acumianata is one of the most common virally transmitted diseases. Its prevalence has increased many fold throughout the world. Because all the currently available treatments yield low cure rates with side effects, the search for a new alternative continues. Topically, 5-fluorouracil (5-FU) has been in used for many years to treat various skin diseases. When applied topically in condyloma acuminata, 5-FU results in low cure rates with high recurrences. Therefore, intralesional 5% 5-FU is being evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…17 The intralesional 5-FU + LE injection was also used for the treatment of genital warts, and the results were 45%-75% complete response in the treatment of patients or lesions. 16,29,30 A previous study found easier and better response rates in common warts than palmoplantar warts. 9 On the other hand, another study reported better responses in palmoplantar warts than common and periungual warts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The intralesional 5-FU + LE injection was also used for the treatment of genital warts, and the results were 45%-75% complete response in the treatment of patients or lesions. 16,29,30 A previous study found easier and better response rates in common warts than palmoplantar warts. 9 On the other hand, another study reported better responses in palmoplantar warts than common and periungual warts.…”
Section: Discussionmentioning
confidence: 99%
“…The intralesional 5‐FU + LE injection was also used for the treatment of genital warts, and the results were 45%–75% complete response in the treatment of patients or lesions 16,29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Nanosystems can also be loaded onto a muco-adhesive in-situ gelling vehicle. The intimate interface between the mucus and gel enables transfer of the nanosystems to the site of action on the vaginal mucosa 78 .…”
Section: Designing a Cervico-vaginal Drug Delivery Systemmentioning
confidence: 99%
“…[3] and Pall et al . [4] However, there have been subtle differences in 5-FU administered by both authors [Table 1]. …”
mentioning
confidence: 99%
“…[6] Recently, intralesional usage of 5-FU at weekly intervals has been utilized for GW. [34] I, however, utilized 5-FU on a monthly basis. The reason for using this schedule was excruciating pain complained by my patient following the first intralesional session.…”
mentioning
confidence: 99%